Separatist Creditors Problems on Postponement of Debt Payment Obligations Based on the Supreme Court’s Decree Number 30/KMA/SK/I/2020 - Suwinto Johan (Universitas Lampung, 2021)
Debt Payment Obligation postponement is an effort for creditors and debtors to settle the debts with a more efficient process. The creditor of a company consists of concurrent and separatist creditors. Based on the Supreme Court Decree Number 30/KMA/SK/I/2020 Book I on the Guidelines for the Settlement of Requests for Bankrupt and Postponement of Debt Payment Obligation of the Supreme Court of the Republic of Indonesia, the creditors who can submit Postponement of Debt Payment Obligation (PKPU) are only concurrent creditors. The separatist creditors are not allowed to submit PKPU. This is different from the Bankruptcy and the Postponement of Debt Payment Law Number 37 of 2004. Based on Law Number 37 of 2004, Creditors who can submit Postponement of Debt Payment Obligation are creditors who estimate that the debtor cannot continue to pay debts that are due and can be billed, can request that the debtor be given a postponement of debt payment, to enable the debtor to submit a reconciliatory proposal which includes offering the payment of part or all of the debt to the creditor. However, based on the Supreme Court Decree, only the concurrent creditor can submit Debt Payment Obligation’s postponement. As a result of this Supreme Court Decree, the separatist creditors cannot apply for Debt Payment Obligation postponement. Separatist creditors can propose the postponement of debt payment obligations if the separatist creditor has turned into a concurrent creditor. Separatist creditors become concurrent creditors if the collateral provided value is insufficient for the company’s obligations so that the separatist creditors can propose to be part of the concurrent creditors. By becoming a concurrent creditor, the separatist creditors can submit to be part of the peace proposal and distribute the remaining company assets.